Experience of loss and grief among people from Germany who have lost their relatives during the pandemic: the impact of healthcare professionals' support - Büssing, Arndt; Baumann, Klaus (Frontiers in Public Health, 2023)
Background: Due to public restrictions during the early stages of the COVID-19 pandemic, many people were unable to visit and bid a proper farewell to their dying loved ones. The aim of this study was to address the loss-oriented aspects of grief and bereavement of relatives and relate these to the support they may have received from their dying relative´s caring professionals.Materials and Methods: In a cross-sectional study using standardized questionnaires (i.e., ICG -Inventory of Complicated Grief; BGL-Burdened by Grief and Loss scale; WHO-5 -WHO-Five Wellbeing Index; 5NRS -perception of burden related to the pandemic) people from Germany who were bereaved during the COVID-19 pandemic were enrolled between July 2021 and May 2022.Results: Most participants (n=196) had the opportunity to visit their relatives before death (59%). When this was not possible, being Burdened by Grief and Loss (BGL) was significantly higher (Eta 2 =0.153), while this had no significant influence on Complicated Grief or psychological wellbeing. 34% of participants felt well supported by the treatment/care team themselves. Their own support was moderately correlated with BGL scores (r=-.38) and marginally with ICG scores (r=-15). Regression analyses showed that Complicated Grief symptoms as the dependent variable were predicted by (low) psychological wellbeing, the relational status, and perception of COVID-19 related burden (R 2 =.70). In contrast, being Burdened by Grief and Loss as the dependent variable was explained best by the perception of emotional affections because of restricted visits shortly before their death, by (short) duration of visits before death, and the relational status (R 2 =.53). Although both are interconnected (r=.44), their predictor pattern is different.Conclusions: Being able to visit the dying relatives was important for the mourning and bereavement processes. This emotional aspect was more relevant for the normal, non-pathological grief and loss processes as compared to complicated grief processes. The support from their dying relatives´ treatment/caring team was highly relevant for the mourning process, but the visiting relatives often lack the information about or have little access to additional resources such as psychologists or pastoral care professionals.